Disproportionality analysis of taste disorders using the FDA adverse event reporting system and Japanese adverse drug event report databases - Kyotani, Yoji; Nakahira, Kiichi; Yoshizumi, Masanori (Frontiers in Pharmacology, 2025)
IntroductionTaste disorders, which can diminish the quality of life and potentially affect drug treatment efficacy, are adverse events that may occur with the use of various medications; however, only a few studies have comprehensively examined this relationship. Spontaneous reporting system-based databases, such as the FDA Adverse Event Reporting System (FAERS) and Japanese Adverse Drug Event Report (JADER), are efficient sources of information for patients treated with drugs; however, analyses using this type of database have some limitations. To address these gaps in knowledge, we comprehensively analyzed the association between drugs and taste disorders using the FAERS and JADER databases.MethodsThe reporting odds ratio (ROR) and Bayesian statistics (Bayesian Confidence Propagation Neural Network, BCPNN) from these databases were used to determine the association between drugs and taste disorders. Weibull distribution and logistic regression were used to investigate the time-to-onset characteristics and odds ratios adjusted for age and sex, respectively, for taste disorders, using data from the FAERS database.Results and discussionOf the 130 drugs for which a signal was detected in both ROR and BCPNN in the FAERS database, 14 had similar signals in the JADER database. Onset time and logistic regression analyses were performed using the FAERS database to characterize drug-induced taste disorders. The median onset time was the same day of administration for nirmatrelvir/ritonavir and clarithromycin; otherwise, it varied among the other drugs. The hazard for clarithromycin remained constant throughout administration, while the hazards for the other drugs decreased over time. Logistic regression analysis confirmed significant associations between the drugs and taste disorders, even after adjusting for age and sex. Overall, these results indicate that certain drugs may be involved in taste disorders, which, depending on their characteristics, warrants further caution and attention. The findings of this study may help healthcare providers recognize drug-induced taste disorders that can lead to a reduced quality of life and noncompliance with medication.